Protein engineering : approaches to the manipulation of protein folding - Narang, Saran A. (Biotechnology (Reading, Mass.) ;, 1990)
Protein Engineering: Approaches to the Manipulation of Protein Folding outlines the complexity of the protein-folding problem and the potential of using genetic tools which, in combination with physical techniques, are expected to shed new light. The book begins with an overview of the basic concepts of protein folding, along with prediction methods and protein-folding models. Separate chapters cover experimental approaches to in vitro protein folding; general approaches used to characterize the folding reaction, equilibrium and kinetic experiments; and strategies employed to elucidate struct.